The development and implementation of a mental toughness training programme for young cricketers - Pattison, Stuart (Rhodes University, Faculty of Humanities, Department of Psychology, 2011)
Modern research being conducted on Mental Toughness is now shifting away from efforts aimed at developing definitions for the construct and instead moving toward efforts at understanding its development. This particular research study focuses on the development and implementation of a Mental Toughness programme designed specifically for, and tailored exclusively to, the needs of schoolboy cricket at Kingswood College in Grahamstown, Eastern Cape. The programme development was an intricate process and the research procedure was guided by the Organisational Development Process model. Data from a focus group as well as various individual interviews were integrated with currently existing Mental Toughness literature and theory to devise this particular Mental Toughness programme. The programme entails educating the athletes on six specific mental skills and incorporates elements of practical application as well as awareness of the importance and influence of Mental Toughness and mental training in a sporting sphere. The programme took the form of mental skills workshops held over a three week period. An analysis was conducted post-programme to document the experience of the athletes as a result of exposure to the programme. Results drawn from the array of analysis procedures were used to help identify the level of success of the Mental Toughness intervention as well as help validify current Mental Toughness models. In addition to highlighting the benefits as a result of the programme experience, various recommendations were drawn in order to shed light on the programme limitations and assist future researchers with understanding the intricacies behind better and more efficient programme implementation.
Keywords: Cricket -- Psychological aspects -- South Africa -- Grahamstown; Cricket -- Training -- South Africa -- Grahamstown; Cricket players -- Mental health -- South Africa -- Grahamstown; Mental discipline; Toughness (Personality trait); Success -- Psychological aspects; Personal coaching -- South Africa -- Grahamstown; School sports -- South Africa -- Grahamstown